EX ANTE REVIEW MELALUI RISET ETNOGRAFI VIRTUAL DALAM PERSPEKTIF LEGISPRUDENSI DI MASA PANDEMI COVID-19 - Edy, Davianus Hartoni (Universitas Ekasakti, 2022)
Virtual ethnography is a research method that examines social phenomena based on the dynamics of netizens observed using certain parameters according to the needs of researchers. In the context of drafting laws, virtual ethnography allows legal researchers to observe, assess, and conclude various phenomena that arise in relation to the public's response to a draft law. Ex ante review is an elaboration of the virtual dynamics of society which, when associated with a legislative perspective, can be an important consideration in preventing the birth of bad legislation due to the dominance of the role of the People's Representative Council who fights for forms of legislation on behalf of certain political sects. The increasing number of active internet users, especially those who access social media, allows ethnographic research methodologies to virtually become an important research object for further study.